Real-Time MRI-guided Radiation Therapy for Locally Advanced Pancreatic Tail Cancer in Contact with The Colon - Yukihiro Hama; Etsuko Tate (http://dharmais.co.id/, 2023)
Introduction: Curative radiation therapy for locally advanced pancreatic ductal adenocarcinoma (PDAC) is difficult when the tumor is in contact with the colon. In this regard, MRI-guided radiation therapy (MRgRT) provides real-time MRI during radiation therapy, resulting in highdose radiation delivery to the target while avoiding surrounding organs at risk (OARs), such as the intestinal tract. Case Presentation: A 94-year-old woman with locally advanced PDAC in the pancreatic tail underwent high-dose (72 Gy/30 fractions) real-time hypo-fractionated MRgRT to avoid irradiation of the colon. Three months after MRgRT, her serum CA 19-9 level normalized, and the tumor regressed completely. No adverse event or recurrence was noted during the six-month follow-up period.Conclusions: High-dose hypo-fractionated MRgRT may be a treatment option for a patient with locally advanced PDAC of the pancreatic tail, which is in contact with the colon.